Policy research on role of traditional medicine in emergency health system construction based on the PMC index model: evidence from China - Yujing Zhang; Xia Tian; Zhao Chen; Ziteng Hu; Huizhen Li; Xingyu Zong; An Li; Fuqiang Zhang; Yaxin Chen; Haili Zhang; Lijiao Yan; Ning Liang; et al. (BMC Complementary Medicine and Therapies)
Abstract Background The integration of traditional Chinese medicine (TCM) into emergency health systems in China serves as a model for global policy development and refining the inclusion of traditional medicine in health emergencies. Methods This study investigated 13 public health emergency policies related to TCM released by the Chinese central government from 2003–2023. A PMC(Policy Modeling Consistency) index model was developed combining ROSTCM text mining analysis software. The contents of these policy documents were quantitatively assessed using 10 first- and 40 s-level indicators. Results The content analysis results showed that current policies focus on emergency treatment, and that the State Administration of Traditional Chinese Medicine is the issuing authority of the main policies, most of which are issued in the form of a notice. The scoring results for the 13 policies showed that two, five, three, and three policies were rated as excellent, good, qualified, and unqualified, respectively. This indicates that the policy quality related to TCM use in emergency response was normally distributed and generally qualified, although room for further improvement exists; policies should follow the principles of science, reasonableness, and operability, and should be updated in a timely manner with continuous development of the governance period while focusing on the policy content, safeguards, and role measures. Conclusion Effective integration of traditional medicine into health emergency policies backed by state institutions is vital. This includes enforcing relevant laws and regulations, establishing multidisciplinary medical teams, and developing integrated medicine strategies that support clinical research and maximize the unique benefits of traditional medicine.